CoxMo(1−x)S2 intermixed reduced graphene oxide as efficient counter electrode materials for high-performance dye-sensitized solar cells. (19th February 2023) - Senthilkumar, R.; Ramakrishnan, Shanmugam; Balu, M.; Batabyal, Sudip K.; Yoo, Dong Jin; Kumaresan, Duraisamy; Kothurkar, Nikhil K.
Abstract: In this study, nanocomposite electrocatalysts composed of cobalt molybdenum sulfide flower-like nanosheets intermixed with reduced graphene oxide (Cox Mo(1−x) S2 /rGO) were prepared by a facile one-step hydrothermal method and were used to prepare counter electrodes (CE) of high-performance dye-sensitized solar cells (DSSCs). The structural and morphological analysis of the nanocomposites were carried out using field emission scanning electron microscopy, micro-Raman, and X-ray photoelectron spectroscopies, which revealed 2-dimensional petal-like nanosheets of the ternary metal sulfides intermixed with the reduced graphene oxide sheets. The DSSCs fabricated using Cox Mo(1−x) S2 /rGO (CMS-2/rGO) as the counter electrode material exhibited power conversion efficiency (PCE) of 9.04%, which was found to be superior to the PCEs of DSSCs with CEs made of MoS2 /rGO (7.56%), Cox Mo(1-x) S2 (7.04–7.78%), and conventional Pt (8.72%). The electrochemical measurements showed that the excellent electrocatalytic activity of the Cox Mo(1−x) S2 /rGO on I3 - can be attributed to the expanded active sites, improved charge transfer across the CE, and reduced electrode/electrolyte interface resistance. The facile preparation approach and outstanding catalytic behavior of Cox Mo(1−x) S2 /rGO indicate that the nanostructured Cox Mo(1-x) S2 /rGO intermix would be a cost-effective material over the platinum used in the CE of DSSCs. Graphical abstract: Image 1 Highlights: Cox Mo(1-x) S2 /rGO hybrids were synthesized by one-step hydrothermal method. Cox Mo(1-x) S2 /rGO hybrids have a high surface area and high electrocatalytic activity. The DSSCs with Cox Mo(1-x) S2 /rGO CEs (PCE = 9.04%) shows a better photovoltaics performance than the Pt (PCE = 8.72%).